2017
DOI: 10.11124/jbisrir-2017-003362
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of bedrails in preventing falls among hospitalized older adults: a systematic review

Abstract: EXECUTIVE SUMMARY Background Falls are a major problem today affecting adults of any age, but the elderly are a population that is more susceptible to falls. Falls are the leading cause of injury or death among older adults. Hospitalized older people are particularly vulnerable to falls. Falls cause direct injuries (minor injuries, severe wounds of the soft tissues and bone fractures) to patients and increased length of stay. The prevention of falls is commonly considered an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 82 publications
1
7
0
Order By: Relevance
“…Bed rails were more common in the Netherlands [29,35,52] and Spain [48] than in Germany [47] and Switzerland [41]. These findings are consistent with previous studies focusing on physical restraint use in nursing homes [20,28,45,66,71]. Although bed rails may seem harmless, and even help one to sleep better by eliminating the fear of falling out of bed, injuries can still occur, such as getting caught between the rails [19,72].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Bed rails were more common in the Netherlands [29,35,52] and Spain [48] than in Germany [47] and Switzerland [41]. These findings are consistent with previous studies focusing on physical restraint use in nursing homes [20,28,45,66,71]. Although bed rails may seem harmless, and even help one to sleep better by eliminating the fear of falling out of bed, injuries can still occur, such as getting caught between the rails [19,72].…”
Section: Discussionsupporting
confidence: 85%
“…Sadly, this scoping review revealed the continuing popularity of physical restraint. According to Marques and colleagues, the prevention of falls is often considered an indicator of quality of care [71]. Therefore, physical restraint may be used to decrease falls and thus make the nursing home staff look good.…”
Section: Discussionmentioning
confidence: 99%
“…On high fall‐risk days, our finding of infrequent restraint assessment by nurses was found to be associated with increased fall‐risk. Although many healthcare professionals regard physical restraint as an option to prevent at‐risk patients from falling (Aranda‐Gallardo et al, 2018), there is some controversy regarding the association between restraint use and falls (Marques, Queiros, Apostolo, & Cardoso, 2017; Sze, Leng, & Lin, 2012). Based on our result that restraint assessment was not related to fall occurrence in the data from the total cohort days, it would appear that restraints are not causally related to fall occurrence in general.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, due to the training and guidance of several health professionals, researchers, and professors in the areas of nursing, medicine, and psychology, 13 systematic reviews have been published in the JBI Evidence Synthesis, being seven systematic reviews of effectiveness (18)(19)(20)(21)(22)(23)(24) , two reviews of reviews (25,26) , one systematic review of qualitative evidence (27) , one systematic review of prevalence and incidence (28) , and two scoping reviews (29,30) . Globally, these reviews address different themes of relevance to the field of nursing, as follows: active aging, differentiated nursing care methodologies (complex), wound care, transitions in health and self-care, and health education and literacy.…”
Section: Pcebp Experience In the Implementation Of The Comprehensive Systematic Review Training Programmentioning
confidence: 99%